Parents' Perceptions and Actions on Digital Safety of Elementary School Students - Hamdan Husein Batubara; Ruruh Sarasati; Amalia Risfianti; Selfi Dewi Rahmawati (Al Ibtida: Jurnal Pendidikan Guru MI)
This study explores parents' perceptions and actions in ensuring the digital safety of elementary school children in Indonesia, where internet penetration is high. This study utilized a mixed methods approach using a convergent parallel design to collect data from 219 parents of elementary school students through closed and open-ended questions presented by Google Forms. Quantitative data was analyzed using mean score and Pearson correlation, whereas quantitative data was analyzed using content and descriptive analysis. The study found that parents generally perceive digital devices and the internet as beneficial tools for enhancing children's learning, creativity, and communication, though they also recognize risks such as exposure to harmful content and cyberbullying. To optimize the benefits and mitigate risks, parents employ strategies such as supervising device use, setting time limits, and educating children about online safety and digital etiquette. These findings highlight the importance of digital literacy for parents and children and the need for collaboration among families, educators, and policymakers to create a safe digital environment for children.